Tolerability, Safety, Pharmacokinetics and Drug Interaction of Cefotaxime Sodium–Tazobactam Sodium Injection (6:1) Following Single and Multiple Intravenous Doses in Chinese Healthy Subjects - Chen, Ning; Sun, Lu-Ning; Hu, Wen-Hui; Wang, Yi-Ya; Xie, Li-Jun; Cheng, Juan; Zhang, Hong-Wen; Liu, Yun; Wang, Yong-Qing; Ding, Li (Frontiers in Pharmacology, 2020)
Purpose: To evaluate the tolerability, safety, pharmacokinetics and drug interaction of cefotaxime sodium-tazobactam sodium injection (6:1) in Chinese healthy subjects. Method: A randomized, single-blind, ascending dose, placebo-controlled, single-center study was conducted. A total of sixty healthy subjects (thirty-eight males, twenty-two females) participated in this study. For the single-dose part, 0.47, 1.17, 2.34, 3.51 and 4.68 g of cefotaxime sodium-tazobactam sodium injection (6:1) were administered. For the multiple-dose part, the subjects administered 2.34 g and 3.51 g of cefotaxime sodium-tazobactam sodium injection (6:1) three times a day for 7 consecutive days. For the drug interaction part, the subjects received 2.0 g of cefotaxime sodium and 0.34 g of tazobactam sodium alone and in combination. Results: Most adverse events and adverse reactions were mild, only two adverse events reported as moderate. The moderate rash was considered of a serious adverse event because of prolonging the hospital stay. The main pharmacokinetic parameters of cefotaxime and tazobactam had no significance difference between 1.17, 2.34, 3.51g dose cohorts and between genders. There was no difference between the trough concentrations on days 6, 7 and 8. The RCmax and RAUC were (0.921±0.070) and (0.877±0.057) for cefotaxime, (0.913±0.046) and (0.853±0.060) for tazobactam, respectively. After cefotaxime and tazobactam were administered alone and in combination, the 90% conﬁdence intervals of the geometric mean ratios for Cmax and AUC were within the predetermined range of 80-125%. In the single-dose part, the renal cumulative excretion ratios were (51.7±6.2)% for cefotaxime, (84.3±8.1)% for tazobactam. There was no significant difference in the maximum excretion rates and the cumulative excretion ratios for cefotaxime and tazobactam, alone or in combination. Conclusions: Cefotaxime sodium-tazobactam sodium injection (6:1) is well-tolerated with the doses from 0.47 to 4.68 g. The pharmacokinetics of cefotaxime and tazobactam were reported as linear over the dose range of 1.17-3.51 g. Cefotaxime was partial excreted via urine while tazobactam was mainly excreted via urine in unchanged form. There was no significant accumulation after administration over 7 consecutive days. The pharmacokinetics and excretion of cefotaxime and tazobactam were not affected by the coadministration of cefotaxime-tazobactam.